Sorptive removal of phenanthrene from aqueous solutions using magnetic and non-magnetic rice husk-derived biochars - Guo, Wei (R Soc Open Sci, 2018)
A magnetically modified rice husk biochar (MBC) was successfully prepared by a hydrothermal method from original biochar (BC) and subsequently used to remove phenanthrene (PHE) from aqueous solutions. The porosity, specific surface area and hydrophobicity of BC were significantly improved (approx. two times) after magnetic modification. The adsorption data fitted well to pseudo-second-order kinetic and Langmuir models. Compared with BC, MBC had a faster adsorption rate and higher adsorption capacity of PHE. The adsorption equilibrium for PHE on MBC was achieved within 1.0 h. The maximum adsorption capacity of PHE on MBC was 97.6 mg g(−1) based on the analysis of the Sips model, which was significantly higher than that of other sources of BCs. The adsorption mechanism of the two BCs was mainly attributed to the action of surface functional groups and π–π-conjugated reactions. The adsorption of PHE on MBC mainly occurred in the functional groups of C–O and Fe(3)O(4), but that on BC was mainly in the functional groups of –OH, N–H, C=C and C–O.